Self-efficacy of emergency management of domestic helpers in pediatric home accidents: A cross-sectional survey in Hong Kong - Ho, Jonathan Ka-Ming; Chung, Jessie Yuk-Seng; Cheung, Shu-Nam; Pang, Winnie Wing-Yan; Yau, Po-Yi; Lam, Simon Ching (Frontiers in Pediatrics, 2022)
Background Accidental injuries are the leading cause of deaths and disabilities in children globally and most of them occur at home. To save life and prevent sequelae, domestic helpers (DHs) require providing emergency management (i.e., first aid) to children involved in home accidents. However, their self-efficacy in emergency management for children is rarely investigated. Hence, this study aimed to tap that research gap. Methods This study adopted a cross-sectional descriptive survey design. A convenience sample of 385 DHs was obtained in Hong Kong. DHs' self-efficacy in emergency management for children involved in home accidents was measured using a 12-item well-validated survey instrument “Self-Efficacy of First Aid in Unintentional Injury at Home”. The total score ranged from 0 to 48. A higher score indicates greater confidence in emergency management for children involved in home accidents. Results All the participants were women and most of them were aged between 31 and 35 years (N = 103, 26.8%). The mean score for DHs' self-efficacy in emergency management was 29.0 (SD 10.1). The three items with the lowest self-efficacy were managing bone fractures, performing cardiopulmonary resuscitation, and providing artificial respiration. Bivariate analysis showed that DHs' self-efficacy was significantly related to their educational level, first aid training, caring experience, and working experience. Multiple linear regression indicated that DHs' educational level (β = 0.136, p = 0.001) and first aid training (β = 0.532, p < 0.001) were significantly predicting their self-efficacy. Conclusion DH's self-efficacy of emergency management for children involved in home accidents was low, particularly in those severe situations and complicated first aid procedures.